TINJAUAN FILOSOFIS UNDANG-UNDANG NOMOR 1 TAHUN 1974 - Prihatinah, Tri Lisiani (Faculty of Law, Universitas Jenderal Soedirman, 2008)
In the globalization era, there is less respect to the marriage institution due to the influence from different concepts of marriages from different countries. In the Indonesian context, one of the reasons comes from misunderstanding towards the nature of family law i.e. Marriage Law Number 1 Year 1974. Better understanding for all Indonesian to the law from phylosophical point of view is an essential effort to achieve the goal of marriage itself. A specific analysis has been given to the aspects of onthology, epistemology and actiology. Kata kunci: filsafat, UU Perkawinan, Indonesia